Does arrival time affect outcomes among severely injured blunt trauma patients at a tertiary trauma centre?. Issue 11 (November 2019) - Brinck, Tuomas; Heinänen, Mikko; Söderlund, Tim; Lefering, Rolf; Handolin, Lauri
Highlights: Three out of four major blunt trauma patients arrive during non-office hours at a tertiary trauma centre. Arrival time does not affect mortality despite the lack of an in-house trauma surgeon consultant available at all times. Units without a 24/7 trauma consultant can maintain a standard of care during non-office hours with protocols and education. Abstract: Background and aims: We aimed to determine whether the outcome of severely injured patients differs based on admission time (office hours vs. non-office hours) at a tertiary trauma centre without an in-house trauma surgeon consultant available at all times. We also studied subgroups of patients presenting with a New Injury Severity Score (NISS) ≥ 25 and patients experiencing major bleeding. Patients and methods: This trauma registry study consisted of severely injured patients (NISS > 15) with blunt trauma treated between 2006 and 2017 at a single institute. Causes of deaths were obtained from autopsy reports and classified as resulting from brain injury; exsanguination; multi-organ failure, adult respiratory distress syndrome, or sepsis; or other. Results: Among 1853 patients, 497 (27%) were admitted during office hours (OH) and 1356 (73%) during non-office hours (NOH). Further subgroup analysis consisted of 211 OH and 611 NOH patients with NISS ≥ 25, and 51 OH and 154 NOH patients experiencing major bleeding. The 30-day in-hospital mortality was 3.8%–7.4% lower in the NOH groups. We found no significant differences between the study groups in neither the standardised mortality ratio (SMR, defined as the ratio of observed to expected mortality) nor in the causes of death. In both groups, the primary cause of death resulted from brain injury. Conclusions: We found that arrival time did not affect mortality among patients with severe blunt trauma treated at a tertiary trauma centre without an in-house trauma surgeon consultant available at all times. Thus, this type of unit can maintain a standard of care during non-office hours by investing in precise treatment protocols and continuous education. However, our results do not apply to penetrating trauma injury patients.